Mapping Philosophical Theories and Methods in Undergraduate Theses at UIN Jakarta: Trends, Approaches, and Contemporary Challenges - Alfadhli Tasman; Muhamad Tamamul Iman; Bambang Irawan; Muhammad Imaduddin (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study examines how philosophy is practiced within the context of Islamic higher education by mapping the theories, methodologies, and approaches found in undergraduate theses at the Faculty of Ushuluddin, UIN Syarif Hidayatullah Jakarta. The research aims to provide an overview of how students engage with classical and contemporary philosophical frameworks to address issues such as globalization, modernity, and pluralism. Adopting a qualitative descriptive design, this study analyzes a corpus of student theses to identify dominant theoretical orientations and methodological tendencies. The findings reveal that Islamic epistemology, ethics, and metaphysics are the most frequently applied theoretical domains. Methodologically, textual analysis and doctrinal approaches dominate, while comparative and hermeneutical methods appear as complementary strategies. Other approaches, including historical, socio-cultural, and ethnographic perspectives, are less common, yet normative-philosophical analysis remains the most prevalent overall. These results suggest that while students demonstrate awareness of contemporary challenges, their engagement is mediated through traditional Islamic philosophical frameworks. This study contributes to discussions on philosophy pedagogy in Islamic higher education and highlights the need for broader methodological diversity to respond effectively to current intellectual and societal issues.